Letters to a young Muslim - Ghobash, Omar Saif, 1971- (New York : Picador, 2017)
"Omar Saif Ghobash was born in 1971 in the United Arab Emirates--the same year the country was founded--to an Arab father and a Russian mother. After a traumatizing experience losing his father to a violent attack in 1977, when he was only six years old, Ghobash began to realize the severe violence that surrounded him in his home country. As he grew older, eventually being appointed as the UAE Ambassador to Russia in 2008, he began to reflect on what it means to be a Muslim, establishing a moral foundation rooted in the belief of the hard grind that is the crux of spiritual and practical living. This book is the result of the personal exploration Ghobash went through in the years after his father's death. The new generation of Muslims is tomorrow's leadership, and yet many are vulnerable to taking the violent shortcut to paradise and ignoring the traditions and foundations of Islam. The burning question, Ghobash argues, is how moderate Muslims will unite and find a voice that is true to Islam while actively and productively engaging in the modern world. Letters to a Young Muslim will explore how Arabs can provide themselves, their children, and their youth with a better chance of prosperity and peace in a globalized world, while attempting to explain the history and complications of the modern-day Arab landscape and how the younger generation can solve problems with extremists internally, contributing to overall world peace"--
The questions you face -- The gray area -- Landscapes of Islam -- Wealth, opportunity, and repentance -- Fragments of memory -- The limits of what we can know -- My first dark days -- Who on Earth told you that? -- What is true Islam? -- "Islam is a religion of peace" -- Crisis of authority -- Responsibility -- The perspective of an outsider -- Path to fundamentalism -- Violence -- Role models -- The challenge of freedom -- Our complex entanglement with the west -- Revelation and reason -- Sermons and what to expect in the mosque on Fridays -- Good deeds and bad deeds -- The Quran and the search for knowledge -- How we construct ourselves and the past -- Men and women -- Free speech and the silence within ourselves -- A closer look at a moral conundrum -- The Muslim individual.
Keywords: Islam -- 21st century; Muslim youth; Islamic sociology; Ghobash, Omar Saif, -- 1971-; Ambassadors -- United Arab Emirates -- Biography; Islam -- 21st century; Autobiographies